Wettability alteration of carbonate rocks via nanoparticle-anionic surfactant flooding at reservoirs conditions - Al-Anssari, S.; Nwidee, L.; Arif, M.; Wang, Shaobin; Barifcani, Ahmed; Lebedev, Maxim; Iglauer, Stefan (2017)
Nanofluids, liquid suspensions of nanoparticles (NPs) dispersed in deionized (DI) water, brine, or surfactant micelles, have become a promising solution for many industrial applications including enhanced oil recovery (EOR) and carbon geostorage. At ambient conditions, nanoparticles can effectively alter the wettability of the strongly oil-wet rocks to water-wet. However, the reservoir conditions present the greatest challenge for the success of this application at the field scale. In this work, the performance of anionic surfactant-silica nanoparticle formulation on wettability alteration of oil-wet carbonate surface at reservoir conditions was investigated. A high-pressure temperature vessel was used to apply nano-modification of oil-wet calcite sample at subsurface conditions (20 MPa, and 70°C). Moreover, to simulate all the potential scenarios inside the oil reservoirs, various concentrations of nanoparticles, surfactant, and salinities were tested. Contact angle measurements on calcite substrates and spontaneous imbibition test on limestone cores were performed to both the natural and modified (oil-wet) samples to consider the effect of heterogeneity and rock complexity on surface wettability. The results showed that formulations of Sodium Dodecylsulfatesilica nanoparticles can alter the wettability of oil-wet calcite to strongly water-wet at reservoir conditions. Further, the spontaneous imbibition data confirmed the role of nano-suspension to render the oil-wet pores to intermediate and water-wet. The findings of this study provide new insights into nanofluids applications for enhanced oil recovery and carbon geo-storage.